Therapeutic and diagnostic implications of exosomes as natural nanoparticles: a new paradigm in brain cancer disease management - Shanid Mohiyuddin; Pankaj Dipankar; Belfin Robinson; Andrew Jeyabose; Andrew Jeyabose; J. Karthikeyan (Frontiers in Medicine)
The clinical translation of safe and effective therapeutic methods for brain cancer treatment is a major challenge that persists in modern medicine. The insufficient drug delivery into the regime of the affected brain tissue due to blood–brain barrier (BBB) restriction leads to a poor prognosis of the disease. However, an alternative strategy using biomaterials like exosomes can offer advancements in the treatment of brain cancer. Exosomes are a type of extracellular microvesicle with a diameter of 30–100 nm, principally functioning as intercellular mediators in the cell signaling process. Due to their biological origin, exosomes demonstrate a significant ability to cross the BBB and possess enhanced biocompatibility, high drug-loading capacity, and low immunogenicity. With the innate property of biomolecule delivery, exosomes also offer enhanced cellular uptake, rendering them exceptional in drug delivery systems. Herein, we focus on the anticancer and diagnostic applications of exosomes for brain cancer therapeutics. The enhancement of the physico-chemical properties of various cell-derived exosomes can be effectively used as a prime drug delivery agent in most treatment strategies. The biphasic and fast drug release in acidic pH of the tumor microenvironment by exosome-mediated drug delivery system contributes to passive targeting, which is often considered advantageous over other drug delivery platforms. These characteristic features are likely to enhance the therapeutic potential and efficacy of the treatment. The exosome loaded with the drug acts as an efficient biomaterial to surpass the BBB, followed by efficient cellular uptake, leading to cytotoxicity in glioblastoma cells. In this review, we summarize the recent updates in theranostic and prognostic strategies using exosomes as a mediator and their prevalence in biomedical applications, with a focus on brain cancer diseases.